The Genre-Based Pedagogical Approach in Indonesian Language Learning at Elementary Schools: Enhancing Reading Literacy Skills - Rohmawati, Aulia; Fauziyah, Giska Eny; Yunaini, Elsa Nenty (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
The Indonesian Language subject plays a vital role in developing students' reading literacy, encompassing language skills such as reading, writing, speaking, and listening. Language proficiency serves as the main foundation of literacy, which involves text comprehension and social practices that support lifelong learning. With strong literacy skills, individuals can critically evaluate information and use it appropriately. In the Kurikulum Merdeka (Independent Curriculum), Indonesian language learning emphasizes the pedagogy genre approach, which focuses on understanding and producing various types of texts according to their communicative purposes. This approach helps students understand the structure and function of language in different contexts, enabling them to develop literacy skills in a more contextual and meaningful way. This article aims to explore in greater depth how the pedagogy genre approach is implemented in Indonesian language learning at elementary and Islamic elementary schools (SD/MI), examine its effectiveness in enhancing students' literacy skills, and identify the challenges faced in its implementation. The research employs both qualitative and quantitative methods. Data were collected through literature studies, field observations, interviews, questionnaires, and analysis of literacy skills through pre-tests and post-tests. The results were analyzed descriptively and quantitatively to gain a comprehensive understanding of the effectiveness of this approach as well as the challenges in its implementation. The findings show that the application of the pedagogy genre approach successfully improved students' reading literacy skills. There was an increase in the number of students in the proficient category from 4 to 14 out of 27 students. Additionally, the number of students in the special intervention category decreased from 8 to 2. Although the improvement was not drastic, it demonstrated a positive impact. This situation reveals several challenges that need to be addressed to optimize the implementation of the pedagogy genre approach. These include the limited availability of reading materials, low student engagement and participation, limited instructional time, low interest and reading habits, and difficulties in assessing learning processes. These challenges should serve as evaluation points to better achieve the goals of the pedagogy genre approach in improving students' literacy and language skills.Keywords: Pedagogy Genre; Literacy Skills; Indonesian Language Learning